The Role of Corporate Communication at PT Busam Media Group in Efforts to Maintain the Company's Positive Image - Sabna Azura; Silviana Purwanti (CV. Publikasi Indonesia, 2026)
This study examines the role of corporate communication of PT Busam Media Group in maintaining a positive image of the company in the midst of fierce media industry competition and information transparency demands. With a qualitative approach of case studies, data is collected through in-depth interviews and documentation from stakeholders in the company. The results of the study show that corporate communication plays a strategic role in developing and implementing effective communication strategies, including two-way communication based on the principle of Excellence theory, information crisis management, and strengthening relationships with stakeholders through social media and CSR programs. The company consistently maintains the quality of news through journalist training and certification, as well as a personalized and balanced approach to communication with sources. An adaptive internal and external communication strategy also helps maintain public trust and a company's reputation. Crisis management is carried out systematically with quick clarification on negative issues. The success of corporate communication is measured by the level of public trust reflected in media interaction and feedback. This research provides theoretical contributions to the understanding of corporate communication and practical recommendations for PT Busam Media Group to optimize communication strategies in maintaining a positive image in the digital era.